Health history: Tuberculosis in letters to esther (São Paulo, 1905-1919) - de Souza Campos, Paulo Fernando [UNESP]; da Silva, Daniele Nunes (My University, 2020)
Objective: In the 1910s, São Paulo, Brazil, was undergoing urban and social transformations that influenced the history of health. They were affected by the fear of epidemics spread throughout the country and killed people without any regard to gender, race and class. The study aims to analyze this historical context from the history of a survivor, Esther de Figueiredo. Method and Sources: Analyzed historical traits, consisting of a set of letters, dated between 1905 and 1919, written by a male to his future wife, make one reflect on diseases and social fear. They also triggered an investigation on the representations of tuberculosis through the history of a person who survived. Results: Results go beyond personal history and accesses aspects inherent to the culture of care within the context of the institutionalization of public health in the city of São Paulo. Conclusions: Tuberculosis was one of the diseases that triggered doctors to search for treatment and cure.
Historia de la salud: Tuberculosis en las cartas a Esther (São Paulo, 1905-1919)
História da saúde: A tuberculose nas cartas para Esther (São Paulo, 1905-1919)
Keywords: Culture of care; Health history; Letter writing; Qualitative research; Tuberculosis